The War in Ukraine, Agricultural Trade and Risks to Global Food Security - Thomas Glauben; Miranda Svanidze; Linde Götz; Sören Prehn; Tinoush Jamali Jaghdani; Ivan Đurić; Lena Kuhn (Intereconomics)
Abstract Any calls to move towards a centrally planned economy or autarky are strongly advised against, as this would only be to the detriment of food security in the Global South.